PENGARUH PENAMBAHAN PROBIOTIK (Lactobacillus sp.) DALAM PAKAN TERHADAP ENERGI METABOLIS, KECERNAAN PROTEIN DAN AKTIVITAS ENZIM BURUNG PUYUH - Dhika Yonika Primacitra; Osfar Sjofjan; Muhammad Halim Natsir (TERNAK TROPIKA Journal of Tropical Animal Production, 2014)
The purpose of this experiment was to know the effect of probiotic (Lactobacillus sp.) supplementation on metabolizable energy, protein digestibility and enzyme activity of quail. This experiment used 20 female quails aged 94 days. Basal diet was comprised of corn, pollard, fish meal, soybean meal, coconut cake, rice bran, lime, salt, premix, lysine and methionine. The basal diet was then supplemented with probiotic at level of 0% (P0), 0,2% (P1), 0,4% (P2) and 0,6% (P3) as treatments. The variables measured were protein digestibility, nitrogen retention, metabolisable energy, N-corrected metabolizable energy, amylase and protease activity enzymes. The experimental applied in this experiment was completely randomized design with four treatments and five replications. The results show that there are no significant effect of probiotic (Lactobacillus sp.)addition (P>0,05) on protein digestibility, nitrogen retention, metabolizable energy and N-corrected metabolizable energy. However, there is significant effect on amylase and protease activity enzymes (P<0,01). It can be concluded that the experiment indicated that supplementation of probiotic (Lactobacillus sp.)in the diet of quails was effective in improving amylase and protease enzymes.   Key words: probiotic, quail, metabolizable energy, protein digestibility, amylase enzyme, protease enzyme.